2011
DOI: 10.1007/s12288-011-0067-1
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Apoptosis in Neutropenic Patients With Hepatitis C Infection: Role of Caspases 3, 10, and GM-CSF

Abstract: Patients with chronic HCV infection are prone to increased susceptibility bacterial infection due to neutropenia complicating the course of this disease. Neutropenia in those patients may stem from enhanced neutrophil apoptosis. However, the molecular mechanism of neutrophil apoptosis has not been clearly defined. Neutrophils harvested from 26 neutropenic patients with hepatitis C infection and nine age and sex-matched healthy control subjects were examined for the degree of apoptosis. Neutrophil apoptosis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Although apoptosis is a default fate of neutrophils, in the inflammatory microenvironment neutrophils are likely exposed to various pro-survival signals, such as LPS (Kebir and Filep, 2013). The defense mechanisms of neutrophils that destroy invading pathogens are also capable of inflicting damage to the surrounding tissue (Nathan, 2006); however, it is not interesting that a medicine may induce neutrophil death since it could become an individual susceptible to severe infections (Tortorella et al, 2001;Salmen et al, 2004;Aref et al, 2011;Break et al, 2012). Consequently, apoptosis induction of neutrophils would comprise a bad side effect of Tag C (1).…”
Section: Discussionmentioning
confidence: 99%
“…Although apoptosis is a default fate of neutrophils, in the inflammatory microenvironment neutrophils are likely exposed to various pro-survival signals, such as LPS (Kebir and Filep, 2013). The defense mechanisms of neutrophils that destroy invading pathogens are also capable of inflicting damage to the surrounding tissue (Nathan, 2006); however, it is not interesting that a medicine may induce neutrophil death since it could become an individual susceptible to severe infections (Tortorella et al, 2001;Salmen et al, 2004;Aref et al, 2011;Break et al, 2012). Consequently, apoptosis induction of neutrophils would comprise a bad side effect of Tag C (1).…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 is responsible for cutting all or part of the key proteins during the implementation stage of apoptosis. Once caspase-3 is activated, cell apoptosis is irreversible [15,16] . Previous studies have shown that caspase-3 activation is an irreversible step in apoptosis and that apoptosis is closely related to tumor occurrence and inhibition [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…In all the studied cases, the mature enzyme is a heterotetramer that contains two p20/p10 heterodimers and two active centers ( 186 ). In neutrophils, caspases 3 and 10 play an important role in the induction of cell death ( 188 ). In Helicobacter pylori -infected neutrophils, the activity of caspase-1 is increased, promoting its association into inflammasomes to participate in the triggering of pyroptosis ( 189 ).…”
Section: Intracellular Mediators Of the Cell Death Of Neutrophilsmentioning
confidence: 99%